An evaluation of a community-based food supplementation for people living with HIV in Ghana: implications for community-based interventions in Ghana - Mensah, Kofi Akohene (BMC Res Notes, 2015)
BACKGROUND: Community-based care and support services are limited in sub-Saharan Africa and as a result a high number of people living with HIV (PLHIV) are not getting the required care and support services. The aim of this study was to assess the impact of food supplementation services for PLHIV in Ghana on weight gained and factors associated with weight gained. METHODS: The study employed mixed methods study design involving quantitative and qualitative techniques. These were structured questionnaire administered to 200 PLHIV selected through simple random sampling and a qualitative component consisting of 14 semi-structured interviews with purposefully selected stakeholders and eight focus group discussions with the beneficiaries. RESULTS: The analysis of the quantitative data showed on average, beneficiaries had gained weight [mean difference in weight was 2 kg with 95 % CI (1.1, 2.9), P value <0.001]. Multivariate analysis showed that the support group to which the beneficiary belonged was the most important determinant of gaining weight. Through the qualitative interviews, beneficiaries indicated that the anti-retroviral drugs were making them hungry and the food helped to alleviate that effect. Notwithstanding, they indicated that the food was nutritious, made them healthy and strong, contributed to their weight gain and was their main sources of hope at home when they had no money. CONCLUSIONS: A broad strategy of food supplementation for PLHIV should be implemented in different ways for different support groups taking into account the differences between different support groups when planning such an intervention. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13104-015-1511-3) contains supplementary material, which is available to authorized users.